2017
DOI: 10.1103/physrevd.96.103511
|View full text |Cite
|
Sign up to set email alerts
|

Echo of interactions in the dark sector

Abstract: We investigate the observational constraints on an interacting vacuum energy scenario with two different neutrino schemes (with and without a sterile neutrino) using the most recent data from CMB temperature and polarization anisotropy, baryon acoustic oscillations (BAO), type Ia supernovae from JLA sample and structure growth inferred from cluster counts. We find that inclusion of the galaxy clusters data with the minimal data combination CMB + BAO + JLA suggests an interaction in the dark sector, implying th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(133 citation statements)
references
References 145 publications
8
119
0
1
Order By: Relevance
“…The cosmological 21-cm line is caused by the hyperfine splitting of neutral hydrogen atoms, whose wavelength corresponds to the transition from the triplet state to the singlet state of the electron. We use the brightness temperature T 21 to describe the strength of the global 1 Cosmological models involving non-gravitational interactions between dark energy and dark matter were extensively studied in literatures [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. For instance see [50] for the early study, see [51] for the alleviation of coincidence problem of the current cosmic acceleration, and see [52] for a review.…”
Section: -Cm Line Brightness Temperature and The Background Evomentioning
confidence: 99%
“…The cosmological 21-cm line is caused by the hyperfine splitting of neutral hydrogen atoms, whose wavelength corresponds to the transition from the triplet state to the singlet state of the electron. We use the brightness temperature T 21 to describe the strength of the global 1 Cosmological models involving non-gravitational interactions between dark energy and dark matter were extensively studied in literatures [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. For instance see [50] for the early study, see [51] for the alleviation of coincidence problem of the current cosmic acceleration, and see [52] for a review.…”
Section: -Cm Line Brightness Temperature and The Background Evomentioning
confidence: 99%
“…However, to alleviate the Coincidence problem and compatibility with the second law of thermodynamics, Q is normally chosen to be positive [17,[35][36][37]. But recently, from an observational point of view, it has been shown that current observational data can favor the late time interaction in the dark sector with Q < 0 [18,38]. It is well known that the above two fluids can be combined as a single fluid having energy density …”
Section: Cosmic Evolution and Thermodynamic Analysismentioning
confidence: 99%
“…One may notice that for δ/β ≪ 1, the equation (28) becomes, H ≃ H 0 exp γβ 2 (t − t 0 ) , and the scale factor becomes double exponential type. However, without imposing any restriction on β and δ, the direct integration of (28) gives the scale factor as 3 One can see the model in equation (176) or equation (3.137) of [35].…”
Section: It Is Clear That If Tanmentioning
confidence: 99%
“…However, the field equations for this theory do not follow from any covariant action. Nevertheless, in the last several years, a series of works towards this direction has been performed with several interesting results [10,11,12,13,14,15,16,17,18,19,20,21,22] and very recently another series of works [23,24,25,26,27,28] showing that the current astronomical data from different independent sources favor the Λ(t) class of models in compared to the concordance ΛCDM cosmology. In view of the observational data, Λ(t) models could be an emerging class of cosmological models, for instance a suitable choice of some models belonging to this class can describe the entire cosmic histroy [16,17,18].…”
Section: Introductionmentioning
confidence: 99%